# Theory Complex

Up to index of Isabelle/HOL

theory Complex
imports Transcendental
(*  Title:       HOL/Complex.thy    Author:      Jacques D. Fleuriot    Copyright:   2001 University of Edinburgh    Conversion to Isar and new proofs by Lawrence C Paulson, 2003/4*)header {* Complex Numbers: Rectangular and Polar Representations *}theory Compleximports Transcendentalbegindatatype complex = Complex real realprimrec Re :: "complex => real"  where Re: "Re (Complex x y) = x"primrec Im :: "complex => real"  where Im: "Im (Complex x y) = y"lemma complex_surj [simp]: "Complex (Re z) (Im z) = z"  by (induct z) simplemma complex_eqI [intro?]: "[|Re x = Re y; Im x = Im y|] ==> x = y"  by (induct x, induct y) simplemma complex_eq_iff: "x = y <-> Re x = Re y ∧ Im x = Im y"  by (induct x, induct y) simpsubsection {* Addition and Subtraction *}instantiation complex :: ab_group_addbegindefinition complex_zero_def:  "0 = Complex 0 0"definition complex_add_def:  "x + y = Complex (Re x + Re y) (Im x + Im y)"definition complex_minus_def:  "- x = Complex (- Re x) (- Im x)"definition complex_diff_def:  "x - (y::complex) = x + - y"lemma Complex_eq_0 [simp]: "Complex a b = 0 <-> a = 0 ∧ b = 0"  by (simp add: complex_zero_def)lemma complex_Re_zero [simp]: "Re 0 = 0"  by (simp add: complex_zero_def)lemma complex_Im_zero [simp]: "Im 0 = 0"  by (simp add: complex_zero_def)lemma complex_add [simp]:  "Complex a b + Complex c d = Complex (a + c) (b + d)"  by (simp add: complex_add_def)lemma complex_Re_add [simp]: "Re (x + y) = Re x + Re y"  by (simp add: complex_add_def)lemma complex_Im_add [simp]: "Im (x + y) = Im x + Im y"  by (simp add: complex_add_def)lemma complex_minus [simp]:  "- (Complex a b) = Complex (- a) (- b)"  by (simp add: complex_minus_def)lemma complex_Re_minus [simp]: "Re (- x) = - Re x"  by (simp add: complex_minus_def)lemma complex_Im_minus [simp]: "Im (- x) = - Im x"  by (simp add: complex_minus_def)lemma complex_diff [simp]:  "Complex a b - Complex c d = Complex (a - c) (b - d)"  by (simp add: complex_diff_def)lemma complex_Re_diff [simp]: "Re (x - y) = Re x - Re y"  by (simp add: complex_diff_def)lemma complex_Im_diff [simp]: "Im (x - y) = Im x - Im y"  by (simp add: complex_diff_def)instance  by intro_classes (simp_all add: complex_add_def complex_diff_def)endsubsection {* Multiplication and Division *}instantiation complex :: field_inverse_zerobegindefinition complex_one_def:  "1 = Complex 1 0"definition complex_mult_def:  "x * y = Complex (Re x * Re y - Im x * Im y) (Re x * Im y + Im x * Re y)"definition complex_inverse_def:  "inverse x =    Complex (Re x / ((Re x)² + (Im x)²)) (- Im x / ((Re x)² + (Im x)²))"definition complex_divide_def:  "x / (y::complex) = x * inverse y"lemma Complex_eq_1 [simp]: "(Complex a b = 1) = (a = 1 ∧ b = 0)"  by (simp add: complex_one_def)lemma complex_Re_one [simp]: "Re 1 = 1"  by (simp add: complex_one_def)lemma complex_Im_one [simp]: "Im 1 = 0"  by (simp add: complex_one_def)lemma complex_mult [simp]:  "Complex a b * Complex c d = Complex (a * c - b * d) (a * d + b * c)"  by (simp add: complex_mult_def)lemma complex_Re_mult [simp]: "Re (x * y) = Re x * Re y - Im x * Im y"  by (simp add: complex_mult_def)lemma complex_Im_mult [simp]: "Im (x * y) = Re x * Im y + Im x * Re y"  by (simp add: complex_mult_def)lemma complex_inverse [simp]:  "inverse (Complex a b) = Complex (a / (a² + b²)) (- b / (a² + b²))"  by (simp add: complex_inverse_def)lemma complex_Re_inverse:  "Re (inverse x) = Re x / ((Re x)² + (Im x)²)"  by (simp add: complex_inverse_def)lemma complex_Im_inverse:  "Im (inverse x) = - Im x / ((Re x)² + (Im x)²)"  by (simp add: complex_inverse_def)instance  by intro_classes (simp_all add: complex_mult_def    distrib_left distrib_right right_diff_distrib left_diff_distrib    complex_inverse_def complex_divide_def    power2_eq_square add_divide_distrib [symmetric]    complex_eq_iff)endsubsection {* Numerals and Arithmetic *}lemma complex_Re_of_nat [simp]: "Re (of_nat n) = of_nat n"  by (induct n) simp_alllemma complex_Im_of_nat [simp]: "Im (of_nat n) = 0"  by (induct n) simp_alllemma complex_Re_of_int [simp]: "Re (of_int z) = of_int z"  by (cases z rule: int_diff_cases) simplemma complex_Im_of_int [simp]: "Im (of_int z) = 0"  by (cases z rule: int_diff_cases) simplemma complex_Re_numeral [simp]: "Re (numeral v) = numeral v"  using complex_Re_of_int [of "numeral v"] by simplemma complex_Re_neg_numeral [simp]: "Re (neg_numeral v) = neg_numeral v"  using complex_Re_of_int [of "neg_numeral v"] by simplemma complex_Im_numeral [simp]: "Im (numeral v) = 0"  using complex_Im_of_int [of "numeral v"] by simplemma complex_Im_neg_numeral [simp]: "Im (neg_numeral v) = 0"  using complex_Im_of_int [of "neg_numeral v"] by simplemma Complex_eq_numeral [simp]:  "(Complex a b = numeral w) = (a = numeral w ∧ b = 0)"  by (simp add: complex_eq_iff)lemma Complex_eq_neg_numeral [simp]:  "(Complex a b = neg_numeral w) = (a = neg_numeral w ∧ b = 0)"  by (simp add: complex_eq_iff)subsection {* Scalar Multiplication *}instantiation complex :: real_fieldbegindefinition complex_scaleR_def:  "scaleR r x = Complex (r * Re x) (r * Im x)"lemma complex_scaleR [simp]:  "scaleR r (Complex a b) = Complex (r * a) (r * b)"  unfolding complex_scaleR_def by simplemma complex_Re_scaleR [simp]: "Re (scaleR r x) = r * Re x"  unfolding complex_scaleR_def by simplemma complex_Im_scaleR [simp]: "Im (scaleR r x) = r * Im x"  unfolding complex_scaleR_def by simpinstanceproof  fix a b :: real and x y :: complex  show "scaleR a (x + y) = scaleR a x + scaleR a y"    by (simp add: complex_eq_iff distrib_left)  show "scaleR (a + b) x = scaleR a x + scaleR b x"    by (simp add: complex_eq_iff distrib_right)  show "scaleR a (scaleR b x) = scaleR (a * b) x"    by (simp add: complex_eq_iff mult_assoc)  show "scaleR 1 x = x"    by (simp add: complex_eq_iff)  show "scaleR a x * y = scaleR a (x * y)"    by (simp add: complex_eq_iff algebra_simps)  show "x * scaleR a y = scaleR a (x * y)"    by (simp add: complex_eq_iff algebra_simps)qedendsubsection{* Properties of Embedding from Reals *}abbreviation complex_of_real :: "real => complex"  where "complex_of_real ≡ of_real"lemma complex_of_real_def: "complex_of_real r = Complex r 0"  by (simp add: of_real_def complex_scaleR_def)lemma Re_complex_of_real [simp]: "Re (complex_of_real z) = z"  by (simp add: complex_of_real_def)lemma Im_complex_of_real [simp]: "Im (complex_of_real z) = 0"  by (simp add: complex_of_real_def)lemma Complex_add_complex_of_real [simp]:  shows "Complex x y + complex_of_real r = Complex (x+r) y"  by (simp add: complex_of_real_def)lemma complex_of_real_add_Complex [simp]:  shows "complex_of_real r + Complex x y = Complex (r+x) y"  by (simp add: complex_of_real_def)lemma Complex_mult_complex_of_real:  shows "Complex x y * complex_of_real r = Complex (x*r) (y*r)"  by (simp add: complex_of_real_def)lemma complex_of_real_mult_Complex:  shows "complex_of_real r * Complex x y = Complex (r*x) (r*y)"  by (simp add: complex_of_real_def)lemma complex_eq_cancel_iff2 [simp]:  shows "(Complex x y = complex_of_real xa) = (x = xa & y = 0)"  by (simp add: complex_of_real_def)lemma complex_split_polar:     "∃r a. z = complex_of_real r * (Complex (cos a) (sin a))"  by (simp add: complex_eq_iff polar_Ex)subsection {* Vector Norm *}instantiation complex :: real_normed_fieldbegindefinition complex_norm_def:  "norm z = sqrt ((Re z)² + (Im z)²)"abbreviation cmod :: "complex => real"  where "cmod ≡ norm"definition complex_sgn_def:  "sgn x = x /⇩R cmod x"definition dist_complex_def:  "dist x y = cmod (x - y)"definition open_complex_def:  "open (S :: complex set) <-> (∀x∈S. ∃e>0. ∀y. dist y x < e --> y ∈ S)"lemmas cmod_def = complex_norm_deflemma complex_norm [simp]: "cmod (Complex x y) = sqrt (x² + y²)"  by (simp add: complex_norm_def)instance proof  fix r :: real and x y :: complex and S :: "complex set"  show "0 ≤ norm x"    by (induct x) simp  show "(norm x = 0) = (x = 0)"    by (induct x) simp  show "norm (x + y) ≤ norm x + norm y"    by (induct x, induct y)       (simp add: real_sqrt_sum_squares_triangle_ineq)  show "norm (scaleR r x) = ¦r¦ * norm x"    by (induct x)       (simp add: power_mult_distrib distrib_left [symmetric] real_sqrt_mult)  show "norm (x * y) = norm x * norm y"    by (induct x, induct y)       (simp add: real_sqrt_mult [symmetric] power2_eq_square algebra_simps)  show "sgn x = x /⇩R cmod x"    by (rule complex_sgn_def)  show "dist x y = cmod (x - y)"    by (rule dist_complex_def)  show "open S <-> (∀x∈S. ∃e>0. ∀y. dist y x < e --> y ∈ S)"    by (rule open_complex_def)qedendlemma cmod_unit_one: "cmod (Complex (cos a) (sin a)) = 1"  by simplemma cmod_complex_polar:  "cmod (complex_of_real r * Complex (cos a) (sin a)) = abs r"  by (simp add: norm_mult)lemma complex_Re_le_cmod: "Re x ≤ cmod x"  unfolding complex_norm_def  by (rule real_sqrt_sum_squares_ge1)lemma complex_mod_minus_le_complex_mod: "- cmod x ≤ cmod x"  by (rule order_trans [OF _ norm_ge_zero], simp)lemma complex_mod_triangle_ineq2: "cmod(b + a) - cmod b ≤ cmod a"  by (rule ord_le_eq_trans [OF norm_triangle_ineq2], simp)lemma abs_Re_le_cmod: "¦Re x¦ ≤ cmod x"  by (cases x) simplemma abs_Im_le_cmod: "¦Im x¦ ≤ cmod x"  by (cases x) simptext {* Properties of complex signum. *}lemma sgn_eq: "sgn z = z / complex_of_real (cmod z)"  by (simp add: sgn_div_norm divide_inverse scaleR_conv_of_real mult_commute)lemma Re_sgn [simp]: "Re(sgn z) = Re(z)/cmod z"  by (simp add: complex_sgn_def divide_inverse)lemma Im_sgn [simp]: "Im(sgn z) = Im(z)/cmod z"  by (simp add: complex_sgn_def divide_inverse)subsection {* Completeness of the Complexes *}lemma bounded_linear_Re: "bounded_linear Re"  by (rule bounded_linear_intro [where K=1], simp_all add: complex_norm_def)lemma bounded_linear_Im: "bounded_linear Im"  by (rule bounded_linear_intro [where K=1], simp_all add: complex_norm_def)lemmas tendsto_Re [tendsto_intros] =  bounded_linear.tendsto [OF bounded_linear_Re]lemmas tendsto_Im [tendsto_intros] =  bounded_linear.tendsto [OF bounded_linear_Im]lemmas isCont_Re [simp] = bounded_linear.isCont [OF bounded_linear_Re]lemmas isCont_Im [simp] = bounded_linear.isCont [OF bounded_linear_Im]lemmas Cauchy_Re = bounded_linear.Cauchy [OF bounded_linear_Re]lemmas Cauchy_Im = bounded_linear.Cauchy [OF bounded_linear_Im]lemma tendsto_Complex [tendsto_intros]:  assumes "(f ---> a) F" and "(g ---> b) F"  shows "((λx. Complex (f x) (g x)) ---> Complex a b) F"proof (rule tendstoI)  fix r :: real assume "0 < r"  hence "0 < r / sqrt 2" by (simp add: divide_pos_pos)  have "eventually (λx. dist (f x) a < r / sqrt 2) F"    using (f ---> a) F and 0 < r / sqrt 2 by (rule tendstoD)  moreover  have "eventually (λx. dist (g x) b < r / sqrt 2) F"    using (g ---> b) F and 0 < r / sqrt 2 by (rule tendstoD)  ultimately  show "eventually (λx. dist (Complex (f x) (g x)) (Complex a b) < r) F"    by (rule eventually_elim2)       (simp add: dist_norm real_sqrt_sum_squares_less)qedinstance complex :: banachproof  fix X :: "nat => complex"  assume X: "Cauchy X"  from Cauchy_Re [OF X] have 1: "(λn. Re (X n)) ----> lim (λn. Re (X n))"    by (simp add: Cauchy_convergent_iff convergent_LIMSEQ_iff)  from Cauchy_Im [OF X] have 2: "(λn. Im (X n)) ----> lim (λn. Im (X n))"    by (simp add: Cauchy_convergent_iff convergent_LIMSEQ_iff)  have "X ----> Complex (lim (λn. Re (X n))) (lim (λn. Im (X n)))"    using tendsto_Complex [OF 1 2] by simp  thus "convergent X"    by (rule convergentI)qedsubsection {* The Complex Number $i$ *}definition "ii" :: complex  ("\<i>")  where i_def: "ii ≡ Complex 0 1"lemma complex_Re_i [simp]: "Re ii = 0"  by (simp add: i_def)lemma complex_Im_i [simp]: "Im ii = 1"  by (simp add: i_def)lemma Complex_eq_i [simp]: "(Complex x y = ii) = (x = 0 ∧ y = 1)"  by (simp add: i_def)lemma norm_ii [simp]: "norm ii = 1"  by (simp add: i_def)lemma complex_i_not_zero [simp]: "ii ≠ 0"  by (simp add: complex_eq_iff)lemma complex_i_not_one [simp]: "ii ≠ 1"  by (simp add: complex_eq_iff)lemma complex_i_not_numeral [simp]: "ii ≠ numeral w"  by (simp add: complex_eq_iff)lemma complex_i_not_neg_numeral [simp]: "ii ≠ neg_numeral w"  by (simp add: complex_eq_iff)lemma i_mult_Complex [simp]: "ii * Complex a b = Complex (- b) a"  by (simp add: complex_eq_iff)lemma Complex_mult_i [simp]: "Complex a b * ii = Complex (- b) a"  by (simp add: complex_eq_iff)lemma i_complex_of_real [simp]: "ii * complex_of_real r = Complex 0 r"  by (simp add: i_def complex_of_real_def)lemma complex_of_real_i [simp]: "complex_of_real r * ii = Complex 0 r"  by (simp add: i_def complex_of_real_def)lemma i_squared [simp]: "ii * ii = -1"  by (simp add: i_def)lemma power2_i [simp]: "ii² = -1"  by (simp add: power2_eq_square)lemma inverse_i [simp]: "inverse ii = - ii"  by (rule inverse_unique, simp)lemma complex_i_mult_minus [simp]: "ii * (ii * x) = - x"  by (simp add: mult_assoc [symmetric])subsection {* Complex Conjugation *}definition cnj :: "complex => complex" where  "cnj z = Complex (Re z) (- Im z)"lemma complex_cnj [simp]: "cnj (Complex a b) = Complex a (- b)"  by (simp add: cnj_def)lemma complex_Re_cnj [simp]: "Re (cnj x) = Re x"  by (simp add: cnj_def)lemma complex_Im_cnj [simp]: "Im (cnj x) = - Im x"  by (simp add: cnj_def)lemma complex_cnj_cancel_iff [simp]: "(cnj x = cnj y) = (x = y)"  by (simp add: complex_eq_iff)lemma complex_cnj_cnj [simp]: "cnj (cnj z) = z"  by (simp add: cnj_def)lemma complex_cnj_zero [simp]: "cnj 0 = 0"  by (simp add: complex_eq_iff)lemma complex_cnj_zero_iff [iff]: "(cnj z = 0) = (z = 0)"  by (simp add: complex_eq_iff)lemma complex_cnj_add: "cnj (x + y) = cnj x + cnj y"  by (simp add: complex_eq_iff)lemma complex_cnj_diff: "cnj (x - y) = cnj x - cnj y"  by (simp add: complex_eq_iff)lemma complex_cnj_minus: "cnj (- x) = - cnj x"  by (simp add: complex_eq_iff)lemma complex_cnj_one [simp]: "cnj 1 = 1"  by (simp add: complex_eq_iff)lemma complex_cnj_mult: "cnj (x * y) = cnj x * cnj y"  by (simp add: complex_eq_iff)lemma complex_cnj_inverse: "cnj (inverse x) = inverse (cnj x)"  by (simp add: complex_inverse_def)lemma complex_cnj_divide: "cnj (x / y) = cnj x / cnj y"  by (simp add: complex_divide_def complex_cnj_mult complex_cnj_inverse)lemma complex_cnj_power: "cnj (x ^ n) = cnj x ^ n"  by (induct n, simp_all add: complex_cnj_mult)lemma complex_cnj_of_nat [simp]: "cnj (of_nat n) = of_nat n"  by (simp add: complex_eq_iff)lemma complex_cnj_of_int [simp]: "cnj (of_int z) = of_int z"  by (simp add: complex_eq_iff)lemma complex_cnj_numeral [simp]: "cnj (numeral w) = numeral w"  by (simp add: complex_eq_iff)lemma complex_cnj_neg_numeral [simp]: "cnj (neg_numeral w) = neg_numeral w"  by (simp add: complex_eq_iff)lemma complex_cnj_scaleR: "cnj (scaleR r x) = scaleR r (cnj x)"  by (simp add: complex_eq_iff)lemma complex_mod_cnj [simp]: "cmod (cnj z) = cmod z"  by (simp add: complex_norm_def)lemma complex_cnj_complex_of_real [simp]: "cnj (of_real x) = of_real x"  by (simp add: complex_eq_iff)lemma complex_cnj_i [simp]: "cnj ii = - ii"  by (simp add: complex_eq_iff)lemma complex_add_cnj: "z + cnj z = complex_of_real (2 * Re z)"  by (simp add: complex_eq_iff)lemma complex_diff_cnj: "z - cnj z = complex_of_real (2 * Im z) * ii"  by (simp add: complex_eq_iff)lemma complex_mult_cnj: "z * cnj z = complex_of_real ((Re z)² + (Im z)²)"  by (simp add: complex_eq_iff power2_eq_square)lemma complex_mod_mult_cnj: "cmod (z * cnj z) = (cmod z)²"  by (simp add: norm_mult power2_eq_square)lemma complex_mod_sqrt_Re_mult_cnj: "cmod z = sqrt (Re (z * cnj z))"  by (simp add: cmod_def power2_eq_square)lemma complex_In_mult_cnj_zero [simp]: "Im (z * cnj z) = 0"  by simplemma bounded_linear_cnj: "bounded_linear cnj"  using complex_cnj_add complex_cnj_scaleR  by (rule bounded_linear_intro [where K=1], simp)lemmas tendsto_cnj [tendsto_intros] =  bounded_linear.tendsto [OF bounded_linear_cnj]lemmas isCont_cnj [simp] =  bounded_linear.isCont [OF bounded_linear_cnj]subsection{*Finally! Polar Form for Complex Numbers*}subsubsection {* $\cos \theta + i \sin \theta$ *}definition cis :: "real => complex" where  "cis a = Complex (cos a) (sin a)"lemma Re_cis [simp]: "Re (cis a) = cos a"  by (simp add: cis_def)lemma Im_cis [simp]: "Im (cis a) = sin a"  by (simp add: cis_def)lemma cis_zero [simp]: "cis 0 = 1"  by (simp add: cis_def)lemma norm_cis [simp]: "norm (cis a) = 1"  by (simp add: cis_def)lemma sgn_cis [simp]: "sgn (cis a) = cis a"  by (simp add: sgn_div_norm)lemma cis_neq_zero [simp]: "cis a ≠ 0"  by (metis norm_cis norm_zero zero_neq_one)lemma cis_mult: "cis a * cis b = cis (a + b)"  by (simp add: cis_def cos_add sin_add)lemma DeMoivre: "(cis a) ^ n = cis (real n * a)"  by (induct n, simp_all add: real_of_nat_Suc algebra_simps cis_mult)lemma cis_inverse [simp]: "inverse(cis a) = cis (-a)"  by (simp add: cis_def)lemma cis_divide: "cis a / cis b = cis (a - b)"  by (simp add: complex_divide_def cis_mult diff_minus)lemma cos_n_Re_cis_pow_n: "cos (real n * a) = Re(cis a ^ n)"  by (auto simp add: DeMoivre)lemma sin_n_Im_cis_pow_n: "sin (real n * a) = Im(cis a ^ n)"  by (auto simp add: DeMoivre)subsubsection {* $r(\cos \theta + i \sin \theta)$ *}definition rcis :: "[real, real] => complex" where  "rcis r a = complex_of_real r * cis a"lemma Re_rcis [simp]: "Re(rcis r a) = r * cos a"  by (simp add: rcis_def)lemma Im_rcis [simp]: "Im(rcis r a) = r * sin a"  by (simp add: rcis_def)lemma rcis_Ex: "∃r a. z = rcis r a"  by (simp add: complex_eq_iff polar_Ex)lemma complex_mod_rcis [simp]: "cmod(rcis r a) = abs r"  by (simp add: rcis_def norm_mult)lemma cis_rcis_eq: "cis a = rcis 1 a"  by (simp add: rcis_def)lemma rcis_mult: "rcis r1 a * rcis r2 b = rcis (r1*r2) (a + b)"  by (simp add: rcis_def cis_mult)lemma rcis_zero_mod [simp]: "rcis 0 a = 0"  by (simp add: rcis_def)lemma rcis_zero_arg [simp]: "rcis r 0 = complex_of_real r"  by (simp add: rcis_def)lemma rcis_eq_zero_iff [simp]: "rcis r a = 0 <-> r = 0"  by (simp add: rcis_def)lemma DeMoivre2: "(rcis r a) ^ n = rcis (r ^ n) (real n * a)"  by (simp add: rcis_def power_mult_distrib DeMoivre)lemma rcis_inverse: "inverse(rcis r a) = rcis (1/r) (-a)"  by (simp add: divide_inverse rcis_def)lemma rcis_divide: "rcis r1 a / rcis r2 b = rcis (r1/r2) (a - b)"  by (simp add: rcis_def cis_divide [symmetric])subsubsection {* Complex exponential *}abbreviation expi :: "complex => complex"  where "expi ≡ exp"lemma cis_conv_exp: "cis b = exp (Complex 0 b)"proof (rule complex_eqI)  { fix n have "Complex 0 b ^ n =    real (fact n) *⇩R Complex (cos_coeff n * b ^ n) (sin_coeff n * b ^ n)"      apply (induct n)      apply (simp add: cos_coeff_def sin_coeff_def)      apply (simp add: sin_coeff_Suc cos_coeff_Suc del: mult_Suc)      done } note * = this  show "Re (cis b) = Re (exp (Complex 0 b))"    unfolding exp_def cis_def cos_def    by (subst bounded_linear.suminf[OF bounded_linear_Re summable_exp_generic],      simp add: * mult_assoc [symmetric])  show "Im (cis b) = Im (exp (Complex 0 b))"    unfolding exp_def cis_def sin_def    by (subst bounded_linear.suminf[OF bounded_linear_Im summable_exp_generic],      simp add: * mult_assoc [symmetric])qedlemma expi_def: "expi z = complex_of_real (exp (Re z)) * cis (Im z)"  unfolding cis_conv_exp exp_of_real [symmetric] mult_exp_exp by simplemma Re_exp: "Re (exp z) = exp (Re z) * cos (Im z)"  unfolding expi_def by simplemma Im_exp: "Im (exp z) = exp (Re z) * sin (Im z)"  unfolding expi_def by simplemma complex_expi_Ex: "∃a r. z = complex_of_real r * expi a"apply (insert rcis_Ex [of z])apply (auto simp add: expi_def rcis_def mult_assoc [symmetric])apply (rule_tac x = "ii * complex_of_real a" in exI, auto)donelemma expi_two_pi_i [simp]: "expi((2::complex) * complex_of_real pi * ii) = 1"  by (simp add: expi_def cis_def)subsubsection {* Complex argument *}definition arg :: "complex => real" where  "arg z = (if z = 0 then 0 else (SOME a. sgn z = cis a ∧ -pi < a ∧ a ≤ pi))"lemma arg_zero: "arg 0 = 0"  by (simp add: arg_def)lemma of_nat_less_of_int_iff: (* TODO: move *)  "(of_nat n :: 'a::linordered_idom) < of_int x <-> int n < x"  by (metis of_int_of_nat_eq of_int_less_iff)lemma real_of_nat_less_numeral_iff [simp]: (* TODO: move *)  "real (n::nat) < numeral w <-> n < numeral w"  using of_nat_less_of_int_iff [of n "numeral w", where 'a=real]  by (simp add: real_of_nat_def zless_nat_eq_int_zless [symmetric])lemma arg_unique:  assumes "sgn z = cis x" and "-pi < x" and "x ≤ pi"  shows "arg z = x"proof -  from assms have "z ≠ 0" by auto  have "(SOME a. sgn z = cis a ∧ -pi < a ∧ a ≤ pi) = x"  proof    fix a def d ≡ "a - x"    assume a: "sgn z = cis a ∧ - pi < a ∧ a ≤ pi"    from a assms have "- (2*pi) < d ∧ d < 2*pi"      unfolding d_def by simp    moreover from a assms have "cos a = cos x" and "sin a = sin x"      by (simp_all add: complex_eq_iff)    hence "cos d = 1" unfolding d_def cos_diff by simp    moreover hence "sin d = 0" by (rule cos_one_sin_zero)    ultimately have "d = 0"      unfolding sin_zero_iff even_mult_two_ex      by (safe, auto simp add: numeral_2_eq_2 less_Suc_eq)    thus "a = x" unfolding d_def by simp  qed (simp add: assms del: Re_sgn Im_sgn)  with z ≠ 0 show "arg z = x"    unfolding arg_def by simpqedlemma arg_correct:  assumes "z ≠ 0" shows "sgn z = cis (arg z) ∧ -pi < arg z ∧ arg z ≤ pi"proof (simp add: arg_def assms, rule someI_ex)  obtain r a where z: "z = rcis r a" using rcis_Ex by fast  with assms have "r ≠ 0" by auto  def b ≡ "if 0 < r then a else a + pi"  have b: "sgn z = cis b"    unfolding z b_def rcis_def using r ≠ 0    by (simp add: of_real_def sgn_scaleR sgn_if, simp add: cis_def)  have cis_2pi_nat: "!!n. cis (2 * pi * real_of_nat n) = 1"    by (induct_tac n, simp_all add: distrib_left cis_mult [symmetric],      simp add: cis_def)  have cis_2pi_int: "!!x. cis (2 * pi * real_of_int x) = 1"    by (case_tac x rule: int_diff_cases,      simp add: right_diff_distrib cis_divide [symmetric] cis_2pi_nat)  def c ≡ "b - 2*pi * of_int ⌈(b - pi) / (2*pi)⌉"  have "sgn z = cis c"    unfolding b c_def    by (simp add: cis_divide [symmetric] cis_2pi_int)  moreover have "- pi < c ∧ c ≤ pi"    using ceiling_correct [of "(b - pi) / (2*pi)"]    by (simp add: c_def less_divide_eq divide_le_eq algebra_simps)  ultimately show "∃a. sgn z = cis a ∧ -pi < a ∧ a ≤ pi" by fastqedlemma arg_bounded: "- pi < arg z ∧ arg z ≤ pi"  by (cases "z = 0", simp_all add: arg_zero arg_correct)lemma cis_arg: "z ≠ 0 ==> cis (arg z) = sgn z"  by (simp add: arg_correct)lemma rcis_cmod_arg: "rcis (cmod z) (arg z) = z"  by (cases "z = 0", simp_all add: rcis_def cis_arg sgn_div_norm of_real_def)lemma cos_arg_i_mult_zero [simp]:     "y ≠ 0 ==> cos (arg(Complex 0 y)) = 0"  using cis_arg [of "Complex 0 y"] by (simp add: complex_eq_iff)text {* Legacy theorem names *}lemmas expand_complex_eq = complex_eq_ifflemmas complex_Re_Im_cancel_iff = complex_eq_ifflemmas complex_equality = complex_eqIend